The utility of the analysis bio-estratigraphic in correlation of the units lithic-estratigraphic of the eocene-miocene in Urabá, Antioquia - Ibáñez-Peña, Fransiner Ricardo (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
From the bioestratigraphic information of the wells: Urabá 1629-IX and Piedrecitas 1570-IX, and the reports published by Ingeominas, the Colombian Mining National Agency it is tested the planktonic foraminipheral utility in the identification of the outcropped units with coal content in the surface, as a hypothesis.  The zone's intense tectonic complexity, linked with the lithic wells reports, added the different conditions of sedimentation of the distinc units, partially disfavor this hypotthesis, due that it was found that the tectonic activities punctured the units and changed the deposits enviromental conditions. At the well Piedrecitas 1570-IX, the species recognized (Globigerinoides extreme, G. slanted, G. immature Globoquadrina altispira, Globorotalia menardii, Neogloboquadrina dutertrei y N. pachyderma) that are related with the late miocene units, and can be halpful to recognize the outcropped coal beds.